How things work. (Alexandria, Va : Time-Life Books, 1989)
Questions and answers provide information about how cameras, elevators, car engines, tops, yo-yos, and other devices work. Includes charts, diagrams, and an activities section.
Keywords: Technology -- Juvenile literature